PEMANFAATAN JAMUR UNTUK PENGENDALIAN NEMATODA PARASIT KOPI ARABIKA - , PUTRI RAHAYU, Dr. Ir. Siwi Indarti, M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The research aimed to test some isolates fungi for controlling plant parasitic nematodes on coffee Arabica. Research were conducted on 2 steps, the first was bioassay of parasitic fungi against Pratylenchus in-vitro, and the second was fungi effectiveness suppress plant parasitic nematodes on Arabica coffee plantation in Afdeling Plalangan, Blawan, Bondowoso, East Java. Four isolates of fungi were used in this research are Fusarium oxysporum isolate KTH 1-3